Azathioprine or 6‐mercaptopurine for induction of remission in Crohn's disease - Chande, Nilesh (Cochrane Database Syst Rev, 2016)
BACKGROUND: The results from controlled clinical trials investigating the efficacy of azathioprine and 6‐mercaptopurine for the treatment of active Crohn's disease have been conflicting and controversial. An updated meta‐analysis was performed to assess the effectiveness of these drugs for the induction of remission in active Crohn's disease. OBJECTIVES: The primary objective was to determine the efficacy and safety of azathioprine and 6‐mercaptopurine for induction of remission in active Crohn's disease. SEARCH METHODS: We searched MEDLINE, EMBASE and the Cochrane Library from inception to 30 October 2015. Review articles and conference proceedings were also searched to identify additional studies. SELECTION CRITERIA: Randomized controlled trials (RCTs) of oral azathioprine or 6‐mercaptopurine compared to placebo or active therapy involving adult patients with active Crohn's disease were selected for inclusion. DATA COLLECTION AND ANALYSIS: Data were extracted by two independent observers based on the intention‐to‐treat principle. Outcomes of interest included: clinical remission, clinical improvement, fistula improvement or healing, steroid sparing, adverse events, withdrawals due to adverse events and serious adverse events. We calculated the pooled relative risk (RR) and 95% confidence intervals (95% CI) for each outcome. The methodological quality of included studies was evaluated using the Cochrane risk of bias tool. The overall quality of the evidence supporting each outcome was assessed using the GRADE criteria. MAIN RESULTS: Thirteen RCTs (n = 1211 patients) of azathioprine and 6‐mercaptopurine therapy in adult patients were identified: nine included placebo comparators and six included active comparators. The majority of included studies were rated as low risk of bias. There was possibly a modest difference in clinical remission rates between azathioprine or 6‐mercaptopurine and placebo. Forty‐eight per cent (95/197) of patients receiving antimetabolites achieved remission compared to 37% (68/183) of placebo patients (5 studies, 380 patients; RR 1.23, 95% CI 0.97 to 1.55; moderate quality evidence). There was possibly a modest difference in clinical improvement rates between azathioprine or 6‐mercaptopurine and placebo. Forty‐eight per cent (107/225) of patients receiving antimetabolites achieved clinical improvement or remission compared to 36% (75/209) of placebo patients (8 studies, 434 patients; RR 1.26, 95% CI 0.98 to 1.62; moderate quality evidence). There was possibly a modest difference in steroid sparing (defined as prednisone dose < 10 mg/day while maintaining remission) between azathioprine and placebo. Sixty‐four per cent (47/73) of azathioprine patients were able to reduce their prednisone dose to < 10 mg/day compared to 46% (32/70) of placebo patients (RR 1.34, 95% CI 1.02 to 1.77; moderate quality evidence). GRADE analyses rated the overall quality of the evidence for the outcomes clinical remission, clinical improvement and steroid sparing as moderate due to sparse data. There was possibly a modest difference in withdrawals due to adverse events or serious adverse events between antimetabolites and placebo. Ten percent of patients in the antimetabolite group withdrew due to adverse events compared to 5% of placebo patients (8 studies, 510 patients; RR 1.70, 95% CI 0.94 to 3.08; moderate quality evidence). Serious adverse events were reported in 14% of patients receiving azathioprine compared to 4% of placebo patients (2 studies, 216 patients; RR 2.57, 95% CI 0.92 to 7.13; low quality evidence). Common adverse events reported in the placebo controlled studies included: allergic reactions. leukopenia, pancreatitis and nausea. Azathioprine was probably inferior to infliximab for induction of steroid‐free clinical remission. Thirty per cent (51/170) of azathioprine patients achieved steroid‐free remission compared to 44% (75/169) of infliximab patients (1 study, 339 patients; RR 0.68, 95% CI 0.51 to 0.90; moderate quality evidence). The combination of azathioprine and infliximab was probably superior to infliximab alone for induction of steroid‐free clinical remission. Sixty per cent (116/194) of patients in the combined azathioprine and infliximab group achieved steroid‐free remission compared to 48% (91/189) of infliximab patients (2 studies, 383 patients; RR 1.23, 95% CI 1.02 to 1.47; moderate quality evidence). Azathioprine or 6‐mercaptopurine therapy was found to be possibly superior at inducing steroid free clinical remission compared to methotrexate (RR 1.13, 95% CI 0.85 to 1.49; low quality evidence) and the evidence was very uncertain as regards the comparison with 5‐aminosalicylate or sulfasalazine (RR 1.24, 95% CI 0.80 to 1.91; very low quality evidence). The estimates for withdrawals due to adverse events between the various drugs were as follows: azathioprine or 6‐mercaptopurine versus methotrexate:RR 0.78, 95% CI 0.23 to 2.71; very low quality evidence; azathioprine or 6‐mercaptopurine versus 5‐aminosalicylate or sulfasalazine: RR 0.98, 95% CI 0.38 to 2.54; low quality evidence; azathioprine versus infliximab: RR 1.47, 95% CI 0.96 to 2.23; moderate quality evidence and the combination of azathioprine and infliximab versus infliximab: RR 1.16, 95% CI 0.75 to 1.80; moderate quality evidence. Common adverse events in the active comparator trials included nausea, abdominal pain, pyrexia and headache. AUTHORS' CONCLUSIONS: Azathioprine and 6‐mercaptopurine possibly offer a modest advantage over placebo for induction of remission or clinical improvement in active Crohn's disease. Antimetabolite therapy possibly allows patients to reduce steroid consumption. Adverse events are possibly more common in patients receiving antimetabolites compared to those receiving placebo. Azathioprine therapy is probably inferior to infliximab for induction of steroid‐free remission. However, the combination of azathioprine and infliximab is probably superior to infliximab alone for induction of steroid‐free remission.